Contesting PLD services: the case of CORE Education - O'Neill JG (Routledge)
The article is derived from a larger study of charities, philanthropists, policy entrepreneurs and international businesses in state schooling in Aotearoa New Zealand. The article considers the formation of a private professional services provider, CORE Education, and its recent corporate trajectory following the government’s decision in 2009 to make all School Support Services provision contestable by private providers. CORE Education is an interesting case of schooling privatization because the organizational structure comprises both a not-for-profit charitable educational trust and a wholly owned, for-profit business. CORE’s activities also illustrate the new network governance modality in schooling. In this modality, both bureaucratic and market forms of schooling services delivery are being displaced by fluid networks of domestic and offshore policy actors who seek strategic and tactical alliances in order to advance their voice and agency in schooling services policy development, delivery and evaluation. The article adopts a critical policy scholarship approach drawing on theories of social network analysis and network policy governance. The article claims that network alliances serve to blur the distinctions between for-profit and not-for-profit activity, between state, NGO and philanthropic actors and, ultimately, between what counts as private and what counts as public in state schooling.